COMMUNITY EMPOWERMENT DIGITALIZATION PROGRAM : TOURISM IN PANGAUBAN VILLAGE, WEST BANDUNG REGENCY, NEW NORMAL ERA - Sutangsa Sutangsa; Lysda Reviyanti (Jurnal Inovasi Penelitian, 2021)
Digital Village is a rural development concept that empowers people with adequate information technology facilities. It is hoped that with the presence of information infrastructure, people can access information on a par with urban communities. In addition, information based on a digital technology system that accommodates all important information related to local agricultural businesses, land data, weather forecasts, development of superior seeds and others, is expected to be able to increase economic growth for the village. An independent village is a village that is able to meet the food and energy needs of the community independently with the support of financial institutions at the rural level that integrate optimally with each other. The purpose of this research is to analyze the Digitalization of Community Empowerment Programs: Tourism in Pangauban Village, West Bandung Regency, Era New Normal. This study uses a qualitative method with a descriptive analysis approach. This research was conducted in Pangauban and Saung Apung Pangaisan Village which is located in Pangauban Village, RT.001 / RW.011, Waduk, Kec. Batujajar, West Bandung Regency, West Java 40561. Digitalization of community empowerment programs in the tourism sector in the new normal era in Pangauban and Saung Apung Pangaisan villages aims to change the situation to be achieved either from a social change which becomes a more empowered, powerful society. also knowledge, technology and ability to be able to better meet their daily needs. The program is carried out through the Digital Village-Desa Wisata (Dedi-Dewi) in collaboration with the Indonesian Education University to advance the economy of Pangauban Village. In addition, the people of Pangauban Village are familiar with technology and have even introduced Pangauban Village and the tourism sector, one of which is Saung Apung Pangaisan through social media Instagram and government websites. Apart from digitalization, in the new normal era, especially community empowerment in the tourism sector, still pay attention to health protocols, continue to open tours by following government recommendations, namely providing hand washing facilities and hand washing soap, detecting visitor temperatures, maintaining distance, reducing operating hours before covid-19 open 24 hours but when new normal opens from 08.00-17.00.